The Cantor Set as an Inverse Limit of Upper Semicontinuous Functions That Are the Union of Mappings - Capul´ın, F; Ruiz del Portal, F R; Sánchez-Garrido, M (Topology Proceedings, 2021)
In this paper, we study the generalized inverse limit with a single upper semi-continuous function $F$ such that it is the union of mappings from a continuum $X$ into itself. Using the concept of $\operatorname{Dom}(F)$, we show that if $X$ has the fixed point property or $X$ is an absolute neighbourhood retract (ANR) space and $\operatorname{Dom}(F)$ is a non-degenerate finite set, the generalized inverse limit is homeomorphic to the Cantor set.